2013
DOI: 10.1007/s10548-013-0327-5
|View full text |Cite
|
Sign up to set email alerts
|

Time–Frequency Analysis of Event-Related Potentials: A Brief Tutorial

Abstract: Event-related potentials (ERPs) reflect cognitive processes and are usually analyzed in the so-called time domain. Additional information on cognitive functions can be assessed when analyzing ERPs in the frequency domain and treating them as event-related oscillations (EROs). This procedure results in frequency spectra but lacks information about the temporal dynamics of EROs. Here, we describe a method-called time-frequency analysis-that allows analyzing both the frequency of an ERO and its evolution over tim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
114
0
6

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 142 publications
(122 citation statements)
references
References 81 publications
2
114
0
6
Order By: Relevance
“…On the other hand, it has been suggested that ERPs are the results of a phase resetting of ongoing oscillatory activity, without changes of EEG power (Makeig et al ., ; see Sauseng et al ., for a review). It has also been suggested that both mechanisms may participate in the generation of ERP components (Herrmann et al ., ). Concerning early visual potentials (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, it has been suggested that ERPs are the results of a phase resetting of ongoing oscillatory activity, without changes of EEG power (Makeig et al ., ; see Sauseng et al ., for a review). It has also been suggested that both mechanisms may participate in the generation of ERP components (Herrmann et al ., ). Concerning early visual potentials (i.e.…”
Section: Discussionmentioning
confidence: 99%
“…While changes in neural oscillations are concealed by the ERP averaging process, a time-frequency decomposition of the single trials used to compute ERPs allows the quantification of event-related spectral changes over time (e.g., Makeig, 1993; Pfurtschneller and Lopes da Silva, 1999; Herrmann et al, 2014). To the extent that event-related oscillations contribute locally to the generation of N1pc, we hypothesize similar hemifield-dependent asymmetric EROs, presumably involving low frequencies in the theta and delta range, as previously observed for an auditory N1 (Kayser et al, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…9 However, this phenomenon cannot be fully captured by averaged event related potentials (ERPs), which probe temporal-spatial dynamics of brain activities. 10 To overcome this limitation, we now applied time frequency analyses to characterize the microsaccade-related spectral power (event-related spectral perturbations [ERSPs]) and phase (intertrial coherence [ITC]). ERSPs measure the time course of relative changes in the spontaneous EEG amplitude spectrum induced by experimental events.…”
mentioning
confidence: 99%